RANCANG BANGUN SISTEM DATA LOGGER DAN MONITORING UNTUK INSTALASI PANEL SURYA GRID TIE (GTI) INVERTER 600 W DENGAN INTERFACING BLYNK - Rafly Akhsani Taqwin; Dista Yoel Tadeus; Fakhruddin Mangkusasmito; Ari Bawono Putranto (BERKALA FISIKA, 2023)
Solar  energy  is  an  inexhaustible  source  of  renewable  energy.  Indonesia,  which  is  a  tropical country  that  is  crossed  by  the  equator,  has  a  fairly  high  solar  intensity  per  year.  With  this potential, it is necessary to process or develop the alternative energy. One way to develop this potential is to use solar panels that can convert solar energy into electrical energy. In this study, we developed a data logger system design tool for the installation of an Arduino-based 600 W inverter grid tie (GTI) solar panel. Nowadays, observation or monitoring still uses conventional or  manual  methods.  Therefore,  in  making  this  task  we  made  a  voltage,  current,  and  power monitoring tool on a solar panel that functions as a current, voltage and power sensor with the Arduino Mega microcontroller as an output data store which will be communicated via Android. The results of the data will be analyzed by calculating the break even point (BEP) to determine the feasibility of procuring On-Grid solar panel systems. From the BEP calculation results, the average energy supply from solar panels is 5% or every month solar panels can reduce costs by Rp.42,000. From these results it is known that the value of the BEP from the procurement of On-Grid solar panels can be achieved for 7 years and 4 months, only then it will be profitable.